The usage of cattle rumen contents in commercial quail feed towards the production and haugh unit (HU) of eggs (Coturnix coturnix japonica) - Joel Jeevan Raj S/O Yogarajah; Tita Damayanti Lestari; Mohammad Anam Al Arif; Widya Paramita Lokapirnasari; Sri Hidanah; Nove Hidajati (Jurnal Agro Veteriner, 2024)
The purpose of this study was to determine the effect of rumen content fermentation on quail bird ration. The parameters measured were the production of egg weight and haugh unit. In total 24 quail birds were used with 4 treatments and 6 repetitions. Treatments were consists of T0(formulated feed without fermented rumen content), T1(formulated feed with 5% fermented rumen content), T2(formulated feed with 10% fermented rumen content), T3(formulated feed with 15% fermented rumen content). Samples are observed on the last day to determine the egg quality with the egg weight and haugh unit. The results showed that there are significant differences effected on the egg weight and haugh unit.